RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF GATIFLOXACIN AND AMBROXOL HCL IN PHARMACEUTICAL DOSAGE FORM - Raul, Saroj Kumar; Shanmukha, Bainapalli; Jhansi, Durgasi (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To develop a simple, selective, linear, precise and accurate RP-HPLC method for simultaneous estimation of Gatifloxacin and Ambroxol HCl in tablet dosage form. Methods: The chromatographic separation was performed using Inerstil ODS-3V (4.6 x 250 mm, 5 Âµm particle size). Mobile phase was composed of phosphate Buffer pH-5 and methanol (40:60v/v) at a flow rate of 1 ml/min. Detection was carried out using PDA detector at 237 nm. The method was validated as per ICH guidelines. Results: The retention times for Gatifloxacin and Ambroxol HCl were observed as 2.443 and 4.863 min respectively. Linearity range was observed in concentration of 32-112 Âµg/ml for Gatifloxacin and 6-21 Âµg/ml for Ambroxol HCl. The percentage recoveries of Gatifloxacin and Ambroxol HCl are 99.64% and 99.78% respectively. The correlation coefficients for both the components are close to 1. Conclusion: This method is simple, selective, linear, precise, accurate and sensitive hence can be successfully employed for the routine quality control of dosage forms containing both the drugs in pharmaceutical industries. Â